Trans-ancestry genome-wide study of depression identifies 697 associations implicating cell types and pharmacotherapies - Adams, Mark J.; Streit, Fabian; Foo, Jerome Clifford; Deuschle, Michael; Frank, Josef; Gilles, Maria; Schulze, Thomas G.; Send, Tabea; Witt, Stephanie; Zillich, Lea; Rietschel, Marcella (Cell, 2025)
In a genome-wide association study (GWAS) meta-analysis of 688,808 individuals with major depression (MD) and 4,364,225 controls from 29 countries across diverse and admixed ancestries, we identify 697 associations at 635 loci, 293 of which are novel. Using fine-mapping and functional tools, we find 308 high-confidence gene associations and enrichment of postsynaptic density and receptor clustering. A neural cell-type enrichment analysis utilizing single-cell data implicates excitatory, inhibitory, and medium spiny neurons and the involvement of amygdala neurons in both mouse and human single-cell analyses. The associations are enriched for antidepressant targets and provide potential repurposing opportunities. Polygenic scores trained using European or multi-ancestry data predicted MD status across all ancestries, explaining up to 5.8% of MD liability variance in Europeans. These findings advance our global understanding of MD and reveal biological targets that may be used to target and develop pharmacotherapies addressing the unmet need for effective treatment.